Pulmonary vein encirclement using an Ablation Index-guided point-by-point workflow: cardiovascular magnetic resonance assessment of left atrial scar formation. Issue 12 (5th September 2019) - O'Neill, Louisa; Karim, Rashed; Mukherjee, Rahul K; Whitaker, John; Sim, Iain; Harrison, James; Razeghi, Orod; Niederer, Steven; Ismail, Tevfik; Wright, Matthew; O'Neill, Mark D; Williams, Steven E
Abstract: Aims : A point-by-point workflow for pulmonary vein isolation (PVI) targeting pre-defined Ablation Index values (a composite of contact force, time, and power) and minimizing interlesion distance may optimize the creation of contiguous ablation lesions whilst minimizing scar formation. We aimed to compare ablation scar formation in patients undergoing PVI using this workflow to patients undergoing a continuous catheter drag workflow. Methods and results: Post-ablation cardiovascular magnetic resonance imaging was performed in patients undergoing 1st-time PVI using a parameter-guided point-by-point workflow ( n = 26). Total left atrial scar burden and the width and continuity of the pulmonary vein encirclement were determined on analysis of atrial late gadolinium enhancement sequences. Comparison was made with a cohort of patients ( n = 20) undergoing PVI using continuous drag lesions. Mean post-ablation scar burden and scar width were significantly lower in the point-by-point group than in the control group (6.6 ± 6.8% vs. 9.6 ± 5.0%, P = 0.03 and 7.9 ± 3.6 mm vs. 10.7 ± 2.3 mm, P = 0.003). More complete bilateral pulmonary vein encirclements were seen in the point-by-point group ( P = 0.038). All patients achieved acute PVI. Conclusion: Pulmonary vein isolation using a point-by-point workflow is feasible and results in a lower scar burden and scar width with more complete pulmonary vein encirclements than a conventional drag lesion approach.